VISUALISASI DINAMIKA PROSES EKSTRAKSI DENGAN FLUIDA SUPERKRITIK - , Hartini
Abstract : This thesis presents a software prototype for the dynamic visualization of extraction process with supercritical fluid which is called LDPEFS Particularly, that dynamic is represented using three kinds of graphical tools including a process flow diagram contrained to operating condition, matter compositions of each flow in a certain time interval, a table and a composition graphic. VDPEFS is designed using data flow oriented and implemented with Borland Delphi version 2.0 and operates on IBM-PC compatibles under Microsoft Windows. The dynamic behavior is derived from the solution of a set of nonlinear ordinary differential equations using Euler or fourth order Runge-Kutta methods. We present also here a generic model PEFS which is develop from the dynamic model PEFS. This model can be used for various matters to be extracted in two-phases system by assigning both the number of tray of extraction column and distillation as process parameters, which in this case tiDPEFS becomes specific. The verification of YDPEFS is accomplished by conducting a number of testings concerning some test factors in each stage of testing. Those stages of testing consist of requirement analysis, design, implementation and using three kinds of test cases including iso-propanol (iPA), 1-butanol, and ethanol. The test result shows that not the whole test factors can be test due to the property of YDPEFS as a prototype. In other hand the testing for the tes cases indicates that I DPEFS works functionally correct.